2015
DOI: 10.1016/j.molcel.2015.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mechanisms of Reinitiation on Bicistronic Calicivirus mRNAs

Abstract: Reinitiation is a strategy used by viruses to express several cistrons from one mRNA. Although extremely weak after translation of long ORFs on cellular mRNAs, reinitiation occurs efficiently on subgenomic bicistronic calicivirus mRNAs, enabling synthesis of minor capsid proteins. The process is governed by a short element upstream of the restart AUG designated “termination upstream ribosomal binding site” (TURBS). It contains the conserved Motif 1 complementary to h26 of 18S rRNA, displayed in the loop of a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
105
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(113 citation statements)
references
References 34 publications
7
105
1
Order By: Relevance
“…Thus, in the absence of eIF3, eIF1 was not able to discriminate against AUGs located too close to the 5 ′ end of mRNA. We previously noted that, in the absence of eIF3, eIF1 was also unable to discriminate efficiently against formation of 48S complexes at near-cognate codons during reinitiation on calicivirus mRNAs (Zinoviev et al 2015). Taken together, this indicates that eIF3 additionally has a role in maintaining the fidelity of initiation codon selection and, with eIF1A, cooperates with eIF1 in this process.…”
Section: Translation Initiation On Capped Mrnasmentioning
confidence: 90%
“…Thus, in the absence of eIF3, eIF1 was not able to discriminate against AUGs located too close to the 5 ′ end of mRNA. We previously noted that, in the absence of eIF3, eIF1 was also unable to discriminate efficiently against formation of 48S complexes at near-cognate codons during reinitiation on calicivirus mRNAs (Zinoviev et al 2015). Taken together, this indicates that eIF3 additionally has a role in maintaining the fidelity of initiation codon selection and, with eIF1A, cooperates with eIF1 in this process.…”
Section: Translation Initiation On Capped Mrnasmentioning
confidence: 90%
“…These capped mRNAs are recognized by eIF4F, which functions to recruit the ribosomal 43S complex containing eIF2a to facilitate translation. However, the ribosomal 43S complex can also bind uncapped mRNAs and internal ribosomal entry sites (IRES) of viral transcripts in conjunction with DENR (Skabkin et al, 2010(Skabkin et al, , 2013Zinoviev et al, 2015). DENR facilitates the efficient translation re-initiation of transcripts bearing an stuORF either by release of deacylated tRNA or recruitment of aminoacylated tRNA (Schleich et al, 2014;Skabkin et al, 2010Skabkin et al, , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…DENR facilitates the efficient translation re-initiation of transcripts bearing an stuORF either by release of deacylated tRNA or recruitment of aminoacylated tRNA (Schleich et al, 2014;Skabkin et al, 2010Skabkin et al, , 2013. Another translation factor, ligatin/eIF2D, contains a SWIB/MDM2 domain homologous to DENR in its N-terminal half, as well as an eIF1-like/SUI domain homologous to MCTS1 in its C-terminal half, and has functions in translation that overlap with those of DENR and MCTS1 (Dmitriev et al, 2010;Skabkin et al, 2010Skabkin et al, , 2013Zinoviev et al, 2015). Whereas it has recently been demonstrated that loss of DENR during Drosophila embryo development leads to impaired tissue growth and larval formation (Schleich et al, 2014), reductions in ligatin gene dosage were found to exacerbate the defective development of DENRknockout flies (Schleich et al, 2014), suggesting overlapping functions for DENR and LIGATIN in embryo development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations